Stability, Bifurcation and Transitions of the Nonlinear Molecular Chain In Electric Field - Lykah, Victor; Syrkin, Eugene (NTU "KhPI", 2016)
The rotational dynamics of molecular adsorbed chain in longitudinal electric field is studied theoretically. The nonlinear dynamic equations are obtained with accounting of quadrupolar interactions between molecules. A new dimensionless parameter (relation of electric and intermolecular interactions) is introduced in the system of the dynamical equations. It is shown that topology of the energy relief on the angle space is transformed in dependence on the electric intensity. The rotational reordering in electric field is complex phenomenon that have several stages. One of the intermediate states is an indifferent equilibrium net (orientation melting). The stable state is found in strong electric fields.
Keywords: molecular chain oscillation; electric field; topology reconstruction